Pleomorphic Adenoma of the Ala Nasi: A Case Report - Mouzali, Amina (Clin Med Insights Ear Nose Throat, 2019)
OBJECTIVES: Pleomorphic adenomas are benign tumors that rarely involve nonsalivary glands. We report an uncommon case of ala nasi pleomorphic adenoma. We discuss the clinical and histopathologic characteristics, and review the literature on nasal pleomorphic adenoma. METHOD: A 20-year-old man presented with a painless slow growing lobulated mass located on the right ala nasi extending into the nasal vestibule. RESULTS: Complete surgical excision was performed. Histologic examination found a mixed cellular component: epithelial and myoepithelial cells with chondromyxoid stroma. This was consistent with the diagnosis of a typical pleomorphic adenoma. There was no evidence of recurrence at 18 months after the surgery. CONCLUSIONS: Pleomorphic adenomas located in the external nose are extremely rare. In such case, pleomorphic adenoma could originate from ectopic minor salivary gland. Complete surgical excision with long-term follow-up is recommended due to the potential risk of recurrence and malignant transformation.